Avoiding the gender trap - Learned, Andrea (Henry Stewart Talks, 2010)
Great marketing need not be gender specific, The future of marketing to women, Today's consumer is human, Gender and consumer behavior, What we know about the new male consumer, Generational differences, What this means in terms of reaching both men and women, Today's core consumer is guided by right brain traits, How to move forward with a focus on common, gender-inclusive ground while very much still using women's buying ways as our guide, Sustainable business practices, The marketplace is undergoing a grand scale cultural shift